2020
DOI: 10.1007/s00265-020-2812-7
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of experimental addition of fresh, aromatic plants into nests of blue tits (Cyanistes caeruleus) on the physiological condition of nestlings

Abstract: The blue tit (Cyanistes caeruleus) is one of a few known passerine birds that incorporate fresh fragments of aromatic plants in their nest during the nesting period. In this study, we experimentally tested whether aromatic plants in blue tit nests affect physiological condition of nestlings as indicated by hemoglobin and glucose in the blood. Nestlings in nests supplemented with fresh, aromatic plants had elevated blood hemoglobin, and therefore improved physiological condition, as compared with control nestli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…There is an increasing number of experimental evidence that morphological and physiological condition of tit nestlings gains when this aromatic plant material is present in the nest (Mennerat et al 2009a(Mennerat et al , 2009bGlądalski et al 2020a;Pires et al 2020). It was also shown that Blue Tits are very choosy when collecting those aromatic plants (Petit et al 2002).…”
Section: Blue Titmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an increasing number of experimental evidence that morphological and physiological condition of tit nestlings gains when this aromatic plant material is present in the nest (Mennerat et al 2009a(Mennerat et al , 2009bGlądalski et al 2020a;Pires et al 2020). It was also shown that Blue Tits are very choosy when collecting those aromatic plants (Petit et al 2002).…”
Section: Blue Titmentioning
confidence: 99%
“…protects against excessive moisture and low temperatures); it may contribute to protection from predators and fix the position of eggs during incubation (Collias & Collias 1984;Deeming 2011;Deeming et al 2012;Lambrechts et al 2016aLambrechts et al , 2016bAkresh et al 2017;Deeming & Campion 2018). In some passerine species, like tits, some nest materials may also serve as parasite repellents and/or antimicrobial agent (Petit et al 2002;Pires et al 2012;Dubiec, Góźdź & Mazgajski 2013;Zabłotni et al 2020;Glądalski et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have looked into whether fresh, aromatic plants in nests influences the physiological conditions of nestlings. Glądalski et al, (2020) experimentally added fresh, aromatic plant fragments into a random sample of Blue Tit nests in Poland. It was found that in the supplemented nests, nestlings had increased levels of haemoglobin when compared to control nests.…”
Section: Introductionmentioning
confidence: 99%
“…This may provide evidence that fresh aromatic plants added by adults improve nestling body conditions and their overall fitness. Glądalski et al, (2020) concluded that more research on properly sensitive physiological indicators is needed to confirm if this is the case. Leaves, when entered as covariates were, found to be significantly influencing and negatively correlating w ith abundance of both ectoparasites.…”
Section: Introductionmentioning
confidence: 99%